NEYROGEN QOVUQ GIPERAKTIVLIGI KASALLIGINI DAVOLASHDA BOTULINOTOKSIN TERAPIYASI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The emergence of botulinum toxin (BT) in the field of medical use has revolutionized the treatment of a number of diseases and aesthetic medicine. Botulinum toxin is the most potent neurotoxin with paralytic/myorelaxant effects. The strongest relaxation properties of this substance are successfully used to treat pathological conditions that cannot be effectively and permanently corrected by other known methods. Many dysfunctions of the lower urinary tract are associated with increased tone or spasms of muscle structures, which can be corrected by precise introduction of BT into the bladder zones. The efficacy and safety of BT for neurogenic overactive bladder have been studied and confirmed in large multicenter studies.